2014
DOI: 10.1007/s00404-014-3255-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients with high-risk pregnancies and complicated deliveries have an increased risk of maternal postpartum readmissions

Abstract: The rate of patients with high-risk pregnancies and complicated deliveries is higher among postpartum maternal readmissions. These data might suggest more cautious postpartum care for those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…CSs are associated with more blood loss, more risk of bladder and ureteral injuries, postpartum infections, pulmonary embolisms, and more risks of neonatal respiratory complications (if performed before 39 weeks). [ 3 4 5 ] In addition, multiple repeat CSs can lead to increased risk of maternal morbidity and mortality because of abnormal placental adherence and cesarean hysterectomy, which increases with each subsequent CS. [ 6 7 ] Such complications are difficult to manage and can cause significant consequences and even maternal death.…”
Section: Introductionmentioning
confidence: 99%
“…CSs are associated with more blood loss, more risk of bladder and ureteral injuries, postpartum infections, pulmonary embolisms, and more risks of neonatal respiratory complications (if performed before 39 weeks). [ 3 4 5 ] In addition, multiple repeat CSs can lead to increased risk of maternal morbidity and mortality because of abnormal placental adherence and cesarean hysterectomy, which increases with each subsequent CS. [ 6 7 ] Such complications are difficult to manage and can cause significant consequences and even maternal death.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified a range of risk factors for readmission, including advanced age, socioeconomic status, chronic comorbidities, multiple gestation, cesarean delivery, and other highrisk pregnancy conditions. 1,4,5 Maternal race may represent a particularly important risk factor for postpartum readmissions and associated complications. Maternal race is a major risk factor adverse obstetric outcomes, and a number of previous analyses have addressed disparities in overall risk for severe morbidity and mortality.…”
mentioning
confidence: 99%
“…In our cohort, postpartum maternal readmission with sepsis within 9 months of delivery occurred in 26 per 100,000 deliveries (95% CI [24][25][26][27][28][29]. Epidemiologic studies from the United States, United Kingdom, and the Netherlands estimated the rate of pregnancy-related sepsis to occur in 9 to 49 per 100,000 deliveries [11][12][13] ; however, these studies did not specifically investigate the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-related readmissions in the postpartum period is an increasing area of interest, but there is a gap in our knowledge on the role of sepsis in these readmissions. [25][26][27][28][29] We found that the majority of readmissions with maternal sepsis were late readmissions, but these readmissions remained associated with events occurring at the delivery hospitalization.…”
Section: Discussionmentioning
confidence: 99%